Design Principles for Safe Human Robot Collaboration. - Laura Tomidei; Matthias Guertler; Nathalie Sick; Gavin Paul; Marc Carmichael (Interaction Design and Architecture(s))
With the development of collaborative robots (cobots), a paradigm shift in human-robot collaboration (HRC) is emerging in the workplace. When introducing cobots, a new range of hazards and harms needs to be considered. While physical hazards have been extensively studied and were paramount in the development of cobots, lesser-known hazards are related to mental and ethical wellbeing. Accordingly, most existing safety measures are designed to address exclusively physical hazards including ergonomics. To this end, this study sets out to develop holistic design principles for safe HRC by adopting a human-centred approach. A systematic review of the relevant literature combined with real-world insights gathered through interviews with industry and academic experts leads to design principles for safe HRC that can contribute to the future development of collaborative robot systems. This also highlights challenges which future research around safety guidelines and standards needs to address.